Phylogenetic relationships in Mediterranean and North Atlantic shearwaters (aves procellariidae) based on nucleotide sequences of mtDNA - Heidrich, Petra; Amengual Ramis, José; Wink, Michael (Biochemical systematics and ecology, 1998)
The mitochondrial cytochrome b gene of Shearwaters (genera Puffinus and Calonectris) from the western, central, and eastern Mediterranean (C. d. diomedea, P. y. yelkouan and P. y. mauretanicus) and the North Atlantic (C. d. borealis, P. puffinus, P. assimilis baroli) was amplified by polymerase chain reaction (PCR) and sequenced directly. Phylogenetic relationships within the group of shearwaters [including published taxa of Austin (1996)] were evaluated with parsimony, likelihood and distance methods. The Balearic Shearwater (P. y. mauretanicus) is a sibling taxon of P. y. yelkouan of eastern and central Mediterranean. Since both taxa are distinguished by several morphological, behavioural and ecological traits, and by 2.2 to 2.9% nucleotide substitutions (which is in the same range as distances between “good” Shearwater species) we consider P. yelkouan and P. mauretanicus distinct species and not subspecies of P. puffinus as assumed earlier. Little Shearwaters of North Atlantic P. assimilis barolis do not share direct ancestry with P. assimilis subspecies of the Southern hemisphere but appear closely related to P. lherminieri. Within the Procellariinae fulmars and shearwaters each represent a monophyletic assemblage. Of the shearwaters studied, Puffinus shows two main monophyletic lineages consisting of the Puffinus subgroup (phylogenetically associated with Calonectris) on the one hand and the subgroups Thyellodroma, Hemipuffinus, Ardenna, Neonectris of the southern hemisphere on the other. Apparently, Puffinus constitutes a paraphyletic taxon, because Calonectris falls between both Puffinus clades. In addition, cytochrome b sequence data show that the three subfamilies of the Procellariidae, i.e. Procellariinae, Hydrobatinae and Diomedeinae, can be recognized as monophyletic groups.
Gesehen am 01.08.2023